(untitled) (Research, Society and Development, 2021)
The aim of the present study is to carry out a bibliographic review regarding oral changes resulting from the use of electronic cigarettes. The PubMed database was used, with the following terms and operators: “electronic cigarette” OR "e-cigarette" OR "electronic cigarettes" AND “oral health” from January 2015 to January 2020. Books were also used and epidemiological data. The inclusion criteria were articles published in Portuguese and / or English, which met the theme proposed by the study. Non-systematic literature reviews and articles that did not strictly refer to the topic were excluded. The final result was a sample of 14 articles, in which 7.14% (n = 1) was classified as a systematic review, 78.57% (n = 11) as an “in vivo” study; 7.14% (n = 1) as a case control study and 7.14% (n = 1) as a pilot study. There was a low level of published evidence on the results of oral health. The effects mentioned referred to periodontal changes and cellular damage to oral tissues. In addition, the use of electronic cigarettes has not demonstrated health security in its entirety.